Dār al-islām, dār al-ḥarb territories, people, identities - Calasso, Giovanna; Lancioni, Giuliano (Studies in Islamic law and society, 2017)
This is the first collection of studies entirely devoted to the terminological pair 'dar al-islam / dar al-harb', "the abode of Islam" and "the abode of war", apparently widely known as representative of "the Islamic vision" of the world, but in fact almost unexplored. A team of specialists in different fields of Islamic studies investigates the issue in its historical and conceptual origins as well as in its reception within the different genres of Muslim written production. In contrast to the fixed and permanent categories they are currently identified with, the multifaceted character of these two notions and their shifting meanings is set out through the analysis of a wide range of contexts and sources, from the middle ages up to modern times